Effectiveness of Flipped Classroom Models in Different Educational Settings: A Systematic Synthesis - St. Fatmah Hiola; Abd Muis (Penelitian dan Pengembangan Ilmu, 2024)
The flipped classroom model, which moves the delivery of material outside the classroom and utilizes class time for interactive activities, has been widely applied at various levels of education. This research aims to evaluate the effectiveness of the flipped classroom model in increasing student engagement at the elementary school (SD), junior high school (SMP), senior high school (SMA), and tertiary levels, as well as in formal and informal education contexts. The systematic literature review (SLR) method was used to synthesize the existing literature, with a focus on studies that address the impact of this model on student engagement in various educational settings. Findings from this study indicate that the flipped classroom can significantly increase student engagement, with differences in effectiveness depending on educational level and educational context. This research concludes that the flipped classroom model has the potential to be an effective method in increasing student engagement, but needs to be adjusted based on the educational context to maximize its benefits.